Performance Analysis of a Universal Circuit for Reversible ALU using QCA & CMOS Technology - Tiwari, Rajinder; kumar, Anil; Shara, Preeta (International Journal of Engineering and Technology, 2018)
The reversible logic and gates are one of the promising and upcoming technologies which are capable of overcoming the limitations of the design and applications based on the CMOS technology. In this technology, the schematic arrangement of the device is implemented in such a way that every input terminal has been provided with individual output terminals. The author has used the technology which is based on quantum computations with a basic feature of loss of energy in small amount. It has many advantages like very high operating speed, low energy dissipation, and high device density. An adder/subtractor is heart of arithmetic units of processors i.e. acts as universal circuit for carrying out the mathematical computations in the quantum processors. The author has put forward a novel reversible adder/subtractor circuit using reversible logic & QCA. The QCA based circuit reported by the author has been compared and analyzed for the performance on the basis of number of gates, size, delay, power dissipation etc. The experimental work has been completed with the use of the most suitable and reliable software i.e. QCA and the performance of the proposed circuit has proven to be quite useful for this circuit to be used in some promising applications. These results are also compared with those obtained with the use of CMOS Technologies.Â Â
Keywords: Reversible Logic; CMOS; Universal Circuit; ALU; Quantum Computing.